Novel Technique Combining Tissue and Mesh Repair for Umbilical Hernia in Adults - Vagholkar, Ketan; Vagholkar, Suvarna (Scientific Research, 2014)
Introduction: Umbilical hernia in adults poses a challenge to the surgeon. Understanding the anatomical and pathological intricacies of the hernia is pivotal in evolving a good repair. A multitude of repairs have been tried for repair of umbilical hernias. However none of them have withstood the test of time. Objective: The study aims at evolving a technique which provides mesh reinforced anatomical reconstruction of the defect. Materials and Methods: 20 patients underwent a combination repair for umbilical hernia. The results were tabulated and analysed. Results: None of the 20 patients developed any recurrence. Conclusion: A combined mesh reinforcement of tissue repair is advocated for umbilical hernias in adults.
Keywords: Anatomical; Tissue; Mesh; Laparoscopic; Repair; Umbilical Hernia